Analysis of the Progressively Enhanced Mine Pressure in the Fully Mechanized Top Coal Caving Work Face of a 20 m Ultra-Thick Coal Seam - Shi Jiulin; Yan Shaohong; Xu Zhuhe; Xue Jisheng; Kaikai Zhao; Zheng Jianwei (Shock and Vibration)
Considering the large mined area, wide strata moving range, strong mine pressure occurrence, and difficult roof control for the fully mechanized top coal caving in 20 m ultra-thick coal seams, this study analyzes the strata structure evolution and mine pressure occurrence behavior through field test, numerical simulation, and theoretical analysis. Based on the mine condition of the Tashan Coal Mine in the Datong mining area, mechanical models are established for the compound overlying structures. The following can be demonstrated from this study: (1) The hard strata can form three different compound spatial structures at different positions in the overlying rock strata, including the lower combined cantilever structure I, the middle combined cantilever structure II, and the upper hinged structure. (2) Failure of the higher structure can induce compression on the lower structure, which changed the break span of the lower structure. (3) “Simultaneous and nonsimultaneous structural failures” of the compound spatial structure were caused by the variation of the break span of the multilayered structure. (4) Based on the weighting characteristics, there were three stages during work face weighting, including a gradual pressure increase stage (Stage I), an accelerated pressure increase stage (Stage II), and a fast pressure increase stage (Stage III). (5) The mine pressure occurrence demonstrated a “small to medium and to large” feature. (6) Prefracturing techniques should be additionally incorporated to prevent simultaneous failure of the multilayered structure. Findings of the work can demonstrate the emergence of strong mine pressure in the Datong mining area and have theoretical significance and reference value for maintaining safe mining in similar conditions.